2015
DOI: 10.1021/jf504722x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Profile of Anthocyanin, Flavonol, and Proanthocyanidin Type, Content, and Localization in Saskatoon Fruits (Amelanchier alnifolia Nutt.)

Abstract: Saskatoons (Amelanchier alnifolia Nutt.) are small fruits that contain substantial quantities of flavonoids. To further characterize and understand the role of these flavonoids during fruit development, anthocyanins, flavonols, and proanthocyanidins were identified, quantified, and localized over development in cultivars that produce blue-purple or white fruit at maturity. Anthocyanin content was low in young fruit and then dramatically increased as the fruit transitioned into ripening only in the pigmented-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…It was observed that the early-maturing cultivars, such as: ‘Kijowska Wczesna’, ‘Harbringer’ and ‘Spring Time’, had higher contents of flavonols than the late-maturing ones (‘Madison’, ‘Flamin Fury’, ‘Harrow Beauty’). Other authors showed no relationship between the content of flavonols and cultivar type (late- or early-maturing), but they observed that the flavonols content decreases as the fruit expanded and matured and also that during storage, especially with access to light, the content of flavonols decreased drastically [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the early-maturing cultivars, such as: ‘Kijowska Wczesna’, ‘Harbringer’ and ‘Spring Time’, had higher contents of flavonols than the late-maturing ones (‘Madison’, ‘Flamin Fury’, ‘Harrow Beauty’). Other authors showed no relationship between the content of flavonols and cultivar type (late- or early-maturing), but they observed that the flavonols content decreases as the fruit expanded and matured and also that during storage, especially with access to light, the content of flavonols decreased drastically [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The identification and concentration results are presented in Table 2 and Figure 1 . The structures of these compounds were identified by comparison of their spectral and MS and/or MS/MS data to those reported in previous studies [ 9 , 18 , 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…“Smoky” was 29% higher than in this cultivar grown in Canada [ 26 ]. According to Jin et al [ 21 ], the contents of anthocyanins in cvs. “Pembina” and “Honeywood” were 50% and 31% lower than in both Saskatoon berry cultivars grown in Poland.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few phytochemical studies of berries across a developmental profile; however, our earlier work on blueberry, as well as studies in Saskatoon berry (Amelanchier alnifolia Nutt.) showed that PA synthesis followed the same pattern: high initial PA levels are diluted out by berry expansion, while de novo synthesis continues throughout maturation (Zifkin et al, 2012;Jin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%